2011
DOI: 10.1590/s0066-782x2010005000161
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de PCR são maiores em pacientes com síndrome coronariana aguda e supradesnivelamento do segmento ST do que em pacientes sem supradesnivelamento do segmento ST

Abstract: Background: There is intense interest in the use of high-sensitivity C-reactive protein (hsCRP) for risk assessment. Elevated hsCRP concentrations early in acute coronary syndrome (ACS), prior to the tissue necrosis, may be a surrogate marker for cardiovascular co-morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
3
10
1
Order By: Relevance
“…Specific to our study design, serum levels of CRP, MMP-9 and MPO have shown significant elevations during the first 48 hours after a myocardial infarction. 4952 In our study, serum and salivary levels of CRP demonstrated changes in concentrations in serum after the ablation procedure. Serum CRP levels rose significantly and progressively suggestive of the myocardial infarction 49 and ongoing inflammation that occurs post-ablation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Specific to our study design, serum levels of CRP, MMP-9 and MPO have shown significant elevations during the first 48 hours after a myocardial infarction. 4952 In our study, serum and salivary levels of CRP demonstrated changes in concentrations in serum after the ablation procedure. Serum CRP levels rose significantly and progressively suggestive of the myocardial infarction 49 and ongoing inflammation that occurs post-ablation.…”
Section: Discussionsupporting
confidence: 56%
“…4952 In our study, serum and salivary levels of CRP demonstrated changes in concentrations in serum after the ablation procedure. Serum CRP levels rose significantly and progressively suggestive of the myocardial infarction 49 and ongoing inflammation that occurs post-ablation. Salivary CRP levels also rose significantly post-ablation, however the increase in concentrations observed were less than those that occurred in serum.…”
Section: Discussionsupporting
confidence: 56%
“…Other studies found no difference in these and other platelet markers (e.g. mean platelet volume, platelet count) [38,39]. However, of the biochemical and physiological mechanisms associated with ambient PM exposure, only thrombus formation and vasoconstriction occur on such a rapid time scale.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the observed variation in CRP concentrations among the types of ACS might be at least partially attributed to the differences in the area of the infarcted myocardium. On the other hand, there are also reports demonstrating lack of significant differences in CRP concentrations at baseline among patients with ACS [24, 25]. It should be also acknowledged that elevated CRP concentration on admission is suggested to be a marker for anatomic complexity of culprit lesions [23, 24].…”
Section: Discussionmentioning
confidence: 99%